Organizing System of Tayub Performance (Case Study in Kabupaten Grobogan in Central Java) - Rachel Mediana Untung (IJCAS (International Journal of Creative and Arts Studies), 2015)
The aim of this study is to figure out a management model of Tayub performance which is performed in Grobogan, Central Java. The research background is Tayub performance is still preserved as a folk art competing with modern art in this modern era. This study is based on sociology and anthropology’s management prespective. This study was conducted in a qualitative research by interviewing several informants. The issue is about early management of functional aspect which includes production management, marketing, human resources and finance. Sociology and anthropology’s perspective sees from the methodology and human’s aspect in management. The results showed that four functions of management have not been implemented well. Yet, Tayub performance can still be performed successfully. The role of dancers, karawitan group, guest leaders, sound and light’s operator also the hosts perform its role professionally. In conclusion, the study found that a successful Tayuban is not about a good management in it but the people themselves who dedicate their abilities, a good understanding in orientation process and highly entrepreneurial spirit. Academically, this research aims to reveal how Tayub’s management model is. Practically, this result can be used by the government to empower socio-economics’ community life as well as to preserve Tayub’s performance.